2020
DOI: 10.1101/2020.08.11.244996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lactoferrin as potential supplementary nutraceutical agent in COVID-19 patients:in vitroandin vivopreliminary evidences

Abstract: The current treatments against SARS-CoV-2 have proved so far inadequate. A potent antiviral drug is yet to be discovered. Lactoferrin, a multifunctional glycoprotein, secreted by exocrine glands and neutrophils, possesses an antiviral activity extendable to SARS-Cov-2. We performed a randomized, prospective, interventional study assessing the role of oral and intra-nasal lactoferrin to treat mild-to-moderate and asymptomatic COVID-19 patients to prevent disease evolution. Lactoferrin induced an early viral cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 113 publications
2
41
0
3
Order By: Relevance
“…In vitro evaluation of the activity of (bovine/human) LF against the virulent SARS-CoV-2 using several cell-lines (Vero E6, Caco-2, adenocarcinoma human alveolar basal epithelial cells, A549, Huh7, HEK293T cell expressing ACE2 (293T-ACE2), HCT-8, Calu-3, and MRC-5 cell lines) clearly showed that LF is capable of inhibition of viral activity, in a dose-dependent manner, via the three aforementioned strategies (Campione et al, 2020b;De Carvalho et al, 2020;Fan et al, 2020;Mirabelli et al, 2020). In addition to these observations, another study emphasized that the anti-SARS-CoV-2 activity is not limited to LF alone, but can be expanded to other components found in total whey milk (Fan et al, 2020).…”
Section: Viral Neutralization (Extracellular Inhibition)mentioning
confidence: 96%
See 2 more Smart Citations
“…In vitro evaluation of the activity of (bovine/human) LF against the virulent SARS-CoV-2 using several cell-lines (Vero E6, Caco-2, adenocarcinoma human alveolar basal epithelial cells, A549, Huh7, HEK293T cell expressing ACE2 (293T-ACE2), HCT-8, Calu-3, and MRC-5 cell lines) clearly showed that LF is capable of inhibition of viral activity, in a dose-dependent manner, via the three aforementioned strategies (Campione et al, 2020b;De Carvalho et al, 2020;Fan et al, 2020;Mirabelli et al, 2020). In addition to these observations, another study emphasized that the anti-SARS-CoV-2 activity is not limited to LF alone, but can be expanded to other components found in total whey milk (Fan et al, 2020).…”
Section: Viral Neutralization (Extracellular Inhibition)mentioning
confidence: 96%
“…bLF formulated in liposomes was used in two different studies on confirmed COVID-19 patients (Campione et al, 2020b;Serrano et al, 2020). Results reported by Serrano et al showed that a liposomal bovine LF supplement containing 32 mg of LF orally administered at 4 to 6 doses/day for 10 consecutive days, accompanied by two to three daily 10 mg zinc doses, resulted in 100% recovery of 75 symptomatic SARS-CoV-2 positive patients within 4-5 days, and the same treatment at lower dose seemed to have prevented the disease in healthy contact (Serrano et al, 2020).…”
Section: Host Immune System Modulation Action Of Lactoferrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, studies on the beneficial effects of orally administered bLf on intestinal flora [ 105 ] and immune system [ 53 ] as well as against infections [ 106 , 107 , 108 , 109 ], inflammation [ 14 , 20 ] and cancers [ 15 , 110 ] strongly support the usefulness of bLf-supplemented foods.…”
Section: Lactoferrin In Natural and Supplemented Foodsmentioning
confidence: 99%
“…Additional computational study sustained the idea of direct LF binding to the Spike S glycoprotein CDT1 domain, reducing the virus's likelihood of entering cells. Moreover, after evaluating the human LF-Spike complex, it was observed that only two residues (Thr500 and Tyr505) are involved in the interface recognition [66]. This protein is mainly produced by the mammalian gland, particularly in mammalian and animal milk [51].…”
Section: Lactoferrinmentioning
confidence: 99%